Numerical simulation of oxygen delivery to muscle tissue in the presence of hemoglobin-based oxygen carriers - Ong, Yong Da (2017)
The human body is made up of seven to eight percent blood. Blood is a vital key to deliver oxygen around the human body. Loss of blood is one of the main cause of death during many severe accidents. Many research has been conducted looking into a substitute for blood or creating artificial blood. Hemoglobin-based oxygen carrier (HBOC) are currently the next most logical alternative for blood. There is currently limited numerical simulation done on oxygen delivery to muscle tissue in the presence of hemoglobin (Hb) based oxygen carrier. In this report the author will be using a chemical species conservation equation, to formulate a transport equation for oxygen delivery. Cross referencing the transport equation to the equation used in the simulation programme, Comsol. Using a 1-dimensional model and stationary study, multiple simulations for the oxygen delivery was conducted. The variables which are altered in the simulation are kinetic dissociation rate coefficient of Hb, Hb concentration, fractural saturation of oxyhemglobin and the diffusion coefficient of oxygen within red blood cells (RBCs). The diffusion coefficient had the greatest impact on the oxygen delivery, followed by the fractural saturation of oxyhemoglobin. The kinetic coefficient and haemoglobin concentration have equal and are the least impactful on oxygen delivery. Overall a change in any variable has a significant impact on the oxygen delivery.